Developing Local Culture–Based Diorama Learning Media to Improve Creativity in Early Childhood - Sitti Khadijah; Herman Herman; Herlina Herlina; Azizah Amal (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
The development of creativity in early childhood education requires innovative and developmentally appropriate learning media, yet culturally relevant instructional resources remain limited. This study aims to develop and evaluate local culture–based diorama media to enhance early childhood creativity. Using a Research and Development (R&D) approach with the Four-D (4D) model, this study involved early childhood learners and teachers at Telkom Makassar Kindergarten. Data were collected through needs analysis, expert validation, teacher responses, and creativity assessments. The results show that the developed diorama media and its guidebook are valid and practical for classroom use and effectively improve children’s creativity. These findings suggest that local culture–based diorama media can serve as an effective alternative learning resource to support creativity development in early childhood education.